Heidelberg Neuro-Music Therapy Enhances Task-Negative Activity in Tinnitus Patients - Krick, Christoph M.; Argstatter, Heike; Grapp, Miriam; Plinkert, Peter K.; Reith, Wolfgang (Frontiers in Neuroscience, 2017)
Background: Suffering from tinnitus causes mental distress in most patients. Recent neuroscientific findings hint at a diminished activity of the brain’s default-mode network (DMN) in the case of psychiatric disorders (e.g., depression or anxiety). In tinnitus, impaired activity of DMN, including the posterior cingulate (PCC) and the precuneus, is said to be involved in tinnitus-associated distress. We have established a rapid therapy approach, the Heidelberg Neuro-Music Therapy (HNMT), which has been shown to considerably reduce tinnitus distress following a one-week short-term treatment. Hence, this therapy option allows for longitudinal observations of the neural changes due to improvements in tinnitus distress. It thus seems fruitful to assess the relationship between compromised DMN-activity and tinnitus-related distress by HNMT. We have previously reported grey matter (GM) reorganization in DMN regions and in primary auditory areas following the HNMT in cases of recent-onset tinnitus. The current study investigated the related activity levels in DMN before and after HNMT using functional MRI (fMRI). Methods: The DMN activity was estimated by the task-negative activation (TNA) during long inter-trial intervals in a word recognition task. The level of TNA was evaluated twice, before and after the one-week study period, in 18 treated tinnitus patients (“treatment goup”, TG), 21 passive tinnitus controls (PTC), and 22 active healthy controls (AC). During the study week, the participants in TG and AC groups were treated with HNMT, whereas PTC patients did not receive any tinnitus-specific treatment. Therapy-related effects on DMN activity were assessed by comparing the pairs of fMRI records from the TG and PTC groups. Results: The comparison between the TG and AC groups, each treated with HNMT, showed tinnitus-specific effects. Both therapy-related effects and tinnitus-specific effects resulted in an augmented DMN activity in the PCC of 2.5% signal change. Following HNMT, the enhancement of the PCC activity was correlated with a reduction in tinnitus distress (Spearman Rho: -0.5; p<0.005). Conclusion: The DMN activity and especially the PCC have been found to be involved in the tinnitus-related therapy effect. In addition, the localization of increased activity in the PCC corresponds with previous findings of structural GM increase by HNMT.